A combined effort of 11 laboratories in the WHO African region to improve quality of Buruli ulcer PCR diagnosis: The "BU-LABNET". - Estelle Marion; Numfor Hycenth; Sundeep Chaitanya Vedithi; Marie Robbe-Saule; Valérie Donkeng; Line-Marlène Ganlonon; Affolabi Dissou; Solange Kakou Ngazoa; Marie-Jose Kabedi; Arsène Mabika Mabika; Richard Phillips; Michael Frimpong; et al. (Public Library of Science (PLoS), 2022)
Buruli ulcer is one of the 20 neglected tropical diseases in the world. This necrotizing hypodermitis is a chronic debilitating disease caused by an environmental Mycobacterium ulcerans. At least 33 countries with tropical, subtropical and temperate climates have reported Buruli ulcer in African countries, South America and Western Pacific regions. Majority of cases are spread across West and Central Africa. The mode of transmission is unclear, hindering the implementation of adequate prevention for the population. Currently, early diagnosis and treatment are crucial to minimizing morbidity, costs and preventing long-term disability. Biological confirmation of clinical diagnosis of Buruli ulcer is essential before starting chemotherapy. Indeed, differential diagnosis are numerous and Buruli ulcer has varying clinical presentations. Up to now, the gold standard biological confirmation is the quantitative PCR, targeting the insertion sequence IS2404 of M. ulcerans performed on cutaneous samples. Due to the low PCR confirmation rate in endemic African countries (under 30% in 2018) for numerous identified reasons within this article, 11 laboratories decided to combine their efforts to create the network "BU-LABNET" in 2019. The first step of the network was to harmonize the procedures and ship specific reagents to each laboratory. With this system in place, implementation of these procedures for testing and follow-up was easy and the laboratories were able to carry out their first quality control with a very high success rate. It is now time to integrate other neglected tropical diseases to this platform, such as yaws or leprosy.